Pendidikan Toleransi Terhadap Remaja Muslim dan Kristen di Salatiga (Studi Terhadap Perayaan Halal Bihalal dan Natal Bersama di Desa Pengilon Mangunsari Sidomukti Kota Salatiga) - Ahmad Faidi (UMSU, 2020)
Cultivating the values of tolerance towards adolescents, especially through the celebration of Islamic and Christian holidays together, is one of the dominant factors in preserving the culture of tolerance among the people of Salatiga City. This type of naturalistic qualitative research, using a critical analytical descriptive approach, makes the people of Pengilon Village as its material objects. This research found that the celebration of Islamic and Christian holidays in Pengilon turned out to have a different function compared to other regions. Apart from functioning as a religious ritual, the Christmas and Halal-Bihalal Celebration